Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
so one way is to subsitute
from the first equation we know that x=3y+5
so we subsitte 3y+5 for x in the second equation
(3y+5)-4y=3
3y+5-4y=3
combine like terms
5-y=3
subtract 5 from both sdies
-y=-2
multiply -1
y=2
subsitute 2 for y
x=3(2)+5
x=6+5
x=11
x=11
y=2
(11,2)
from the first equation we know that x=3y+5
so we subsitte 3y+5 for x in the second equation
(3y+5)-4y=3
3y+5-4y=3
combine like terms
5-y=3
subtract 5 from both sdies
-y=-2
multiply -1
y=2
subsitute 2 for y
x=3(2)+5
x=6+5
x=11
x=11
y=2
(11,2)
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.